Investigation of a seat suspension installed with compact variable stiffness and damping rotary magnetorheological dampers. (15th May 2022) - Deng, Lei; Sun, Shuaishuai; Christie, Matthew; Ning, Donghong; Jin, Shida; Du, Haiping; Zhang, Shiwu; Li, Weihua
Highlights: A novel compact rotary MR damper with variable stiffness and variable damping characteristics was designed and prototyped for the seat suspension. The nonlinear stiffness control scheme can avoid the end-stop impact and dissipate vibration energy. The no-jerk skyhook damping control scheme can reduce the vibration amplitude. The vibration attenuation performance of the seat suspension was largely improved by the VSVD rotary MR damper. Abstract: Long-term vibration poses a threat to drivers' health and affects their ride performance. Furthermore, large-magnitude vibration and sudden shocks may even result in end-stop impacts, raising the drivers' injury risk. To reduce the vibration and avoid end-top impacts, this paper presents an innovative seat suspension installed with variable stiffness and variable damping (VSVD) rotary magnetorheological (MR) dampers. At first, a novel compact VSVD rotary MR damper was designed and prototyped for the suspension, making the suspension's stiffness and damping controllable. Then, with two identical VSVD MR dampers were installed, the prototyped seat suspension was characterised by an MTS test frame to verify its capabilities of variable stiffness and damping. A control strategy consisting of a nonlinear stiffness control and a no-jerk skyhook damping control was also designed. Finally, the vibration attenuation performance of the seat suspension was numerically and experimentally evaluated under three vibration excitations, i.e., harmonic excitation, bump excitation, and random excitation. Both numerical and experimental results indicate that the vibration control performance of the seat suspension can be significantly improved by the VSVD rotary MR dampers.